Microsoft Inc.- Strategic audit : Key performance indicator and competitor analysis - Pandey, Bankim ([Place of publication not identified] : [publisher not identified], 2017)
Porter$1 (Bs five forces Model analysis of Microsoft Corporation Threat of New entrant$1 (Bs- In software field threat of new entrant is much, because as the technology changes new players emerge in the market. Earlier Microsoft misses the tidal waves, but now in its changed policy it left behind the Netscapes. Microsoft seems to struggle with open source software such as Linux, but now Microsoft working on more open source development model rather than controlling it. Microsoft now feels that it$1 (Bs better to be part of change rather to obstruct it because in software field we cannot restrict new technology for a long time. Bargaining power of supplier-In this field is quite low .The bargaining power of Microsoft is still better than its competitor because a type of monopoly this company enjoy is unique in this field Bargaining power of Customers-In software field number of players is large so the customer has more option to fulfil their needs. Bargaining power of customer in this sector is high. Threat of substitute-High in this field, there is chance of copying of the product. New players are offering new innovative products. Microsoft has adopted New Activation method for its software duplication protection. Rivalry among Existing firms-High in this field. For Example- Apache Web Server (Open source model) software dominates the market for Web server software. Microsoft responded to this situation by bundling Internet Information Server free with Windows NT and 2000 Server. The emergence of Linux is new threat Microsoft responded it by developing Dot (.) net strategy for internet framework.s
Strategic Audit of Microsoft -- Introduction of organization -- Identification of the industry & competitors -- Analysis of microsoft competitors -- Analysis of industry -- Porter's five force model -- Analysis of Macro environment -- Threat & opportunities --Analysis of organization measurement & control system -- Key performance indicators -- Organisational mission, vision & core values -- Organisational & business level strategies -- SWOT Analysis -- Functional strategies -- Improvement & Change initiatives -- Balance scorecard list of awards -- Conclusion -- Reference.
Keywords: STRATEGIC PLANNING